2020
DOI: 10.1002/macp.202000023
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of a Fluorine‐Free, Robust, Superhydrophobic Coating through Dip Coating Combined with Non‐Solvent Induced Phase Separation (Dip‐Coating‐NIPS) Method

Abstract: Superhydrophobic surfaces based on non‐fluorinated materials and facile fabrication techniques are of great practical value with respect to environmental friendliness and industrial applications. In this work, a fluorine‐free, superhydrophobic coating with hierarchical surface structure and low surface energy is successfully fabricated on various substrates through a recently developed dip coating combined with non‐solvent induced phase separation (dip‐coating‐NIPS) method. A bio‐based polymer, poly(l‐lactic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In addition to the above-discussed sol-gel method, molding method, etching method and deposition method, there are some other methods that can prepare multiscale-structured superhydrophobic surfaces of non-metallic materials, such as the electrospinning method [140][141][142][143][144][145], the self-assembly method [146][147][148][149][150], the spraying method [151][152][153], the dip-coating method [154,155] and so on. As shown in Figure 9A, Gan et al [140] used a sequential electrospinning and electrospraying method to fabricate composite membranes of polystyrene-block-poly (ethylene-co-butylene)-block-polystyrene (SEBS) and fluorinated polyhedral oligomeric silsesquioxane-block-polystyrene (FPOSS-PS).…”
Section: Other Methodsmentioning
confidence: 99%
“…In addition to the above-discussed sol-gel method, molding method, etching method and deposition method, there are some other methods that can prepare multiscale-structured superhydrophobic surfaces of non-metallic materials, such as the electrospinning method [140][141][142][143][144][145], the self-assembly method [146][147][148][149][150], the spraying method [151][152][153], the dip-coating method [154,155] and so on. As shown in Figure 9A, Gan et al [140] used a sequential electrospinning and electrospraying method to fabricate composite membranes of polystyrene-block-poly (ethylene-co-butylene)-block-polystyrene (SEBS) and fluorinated polyhedral oligomeric silsesquioxane-block-polystyrene (FPOSS-PS).…”
Section: Other Methodsmentioning
confidence: 99%
“…Surface modification is an efficient way to change the surface characteristics of a membrane, such as surface energy, functionality and roughness, to increase the hydrophobicity of the membrane. 70 To date, various surface modification technologies have been used, such as surface coating, 79 dip coating 80 and chemical vapor deposition, 81 to improve the surface hydrophobicity of membranes.…”
Section: Post-treatment Modification Of Membrane Surfacementioning
confidence: 99%
“…In addition, the introduction of other substances would also certainly have an impact on the biodegradability of CA films. It has been well known that constructing micro/nano-scale roughness plays an important role in regulating the wettability of a material surface. A variety of surface roughness constructing methods have been developed, including but not limited to the template method, electrospinning, phase separation method, plasma treatment method, spin coating method, breath figure method, etching method, and self-assembly method. ,, Among these surface roughness constructing methods, the nonsolvent-induced phase separation (NIPS) method, in which polymer solution self-organizes and generates microscopic polymer-rich and -poor phases due to the exchange of nonsolvent and solvent, is a simple, low-cost but quite an effective method to achieve micro/nano-scale surface roughness, which could lead to superhydrophobic surfaces. For instance, Xue et al have reported a simple method for preparing rose petal-like quasi-superhydrophobic polylactide acid (PLA) film surfaces with adjustable water droplet adhesion characteristics through a NIPS process based on PLA-based stereo composite cocrystallization . Xu et al have prepared a superhydrophobic stereo complex PLA (Sc-PLA) film with multiscale microstructures by NIPS, which results in water contact angles (WCAs) as high as 151.5° .…”
Section: Introductionmentioning
confidence: 99%
“…It has been well known that constructing micro/ nano-scale roughness plays an important role in regulating the wettability of a material surface. 15−18 A variety of surface roughness constructing methods have been developed, including but not limited to the template method, 19 electrospinning, 20 phase separation method, 21 method, 22 spin coating method, 23 breath figure method, 24 etching method, 25 and self-assembly method. 14,26,27 Among these surface roughness constructing methods, the nonsolventinduced phase separation (NIPS) method, in which polymer solution self-organizes and generates microscopic polymer-rich and -poor phases due to the exchange of nonsolvent and solvent, is a simple, low-cost but quite an effective method to achieve micro/nano-scale surface roughness, which could lead to superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%